The Role of Fiqh Teachers in Enhancing the Implementation of Congregational Dhuhr Prayer at Madrasah Tsanawiyah An Nuur Sengon Sari Asahan Regency - Suhardi Suhardi; Abdul Kholik; Syawaluddin Damanik; Kenny Agusto Ariewibowo; Herlina Pertiwi (Continuous Education: Journal of Science and Research, 2026)
The implementation of congregational Dhuhr prayer in Islamic educational institutions plays a strategic role in shaping students' religious character and discipline. However, its effectiveness is highly dependent on the role and professionalism of Fiqh teachers as key agents of religious habituation. This study aims to analyze the role of Fiqh teachers, identify supporting and inhibiting factors, examine the impact of congregational Dhuhr prayer on students' character development, and formulate strategies for optimizing the contribution of Fiqh teachers in strengthening religious practices at school. The research employs a qualitative approach with a field research design conducted at Madrasah Tsanawiyah Annur Sengon Sari, Asahan Regency. Data were collected through observation, indepth interviews, and documentation studies. Data analysis used descriptive qualitative technique supported by triangulation to ensure validity. The findings indicate that Fiqh teachers play a pivotal role as educators, role models, and facilitators of religious culture through exemplary behavior, integration of Fiqh instruction with practical worship, persuasive guidance, and collaborative engagement with the school community. Congregational Dhuhr prayer contributes significantly to strengthening students' religious character, discipline, social cohesion, and moral awareness.